The urban climate system and the impacts of flooding on Rio de Janeiro, Brazil - Armond, Nubia Beray; Sant'Anna Neto, João Lima [UNESP] (Springer Nature, 2019)
Despite their individual socio-spatial paths of development, the countries of Latin America underwent similar urbanization processes. Analyzed from the geographical perspective of the spatial relationship between society and nature, the different forms of urbanization, especially in their material dimension, directly affect the creation of different climates. Based on this assumption, Carlos Augusto de Figueiredo Monteiro originally proposed, in his associate professorship thesis, the Urban Climate System (UCS) theory in Brazil with the goal of analyzing the climates of specific locations and their urbanization. Based on the work by Monteiro, combined with a climate geographical perspective, the goal of our study was to analyze the urban climate, specifically the hydrometeorological subsystem that triggers extreme events in the urban portion of Rio de Janeiro, Brazil. First, the specifics of urbanization of a Latin American metropolis underlining the particularities of its urban climate are briefly introduced. Subsequently, the UCS theory is presented, focusing on the perceptual channels and the specifics of flood events, which is followed by a characterization of the climate dynamics of the study area, including those that occur on an hourly scale. Last, the hours of highest precipitation are identified, and the ways in which social groups are related to the urban climate of Rio de Janeiro are explained.
Keywords: Flooding; Geographic climatology; Precipitation; Rio de Janeiro; Urban climate